Motivated Political Reasoning: On the Emergence of Belief-Value Constellations - Kai Barron; Anna Becker; Steffen Huck (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2024)
We study the relationship between moral values ("ought" statements) and factual beliefs ("is" statements). We show that thinking about values affects the beliefs people hold. This effect is mediated by prior political leanings, thereby contributing to the polarization of factual beliefs. We document these findings in a pre-registered online experiment with a nationally representative sample of over 1,800 individuals in the US. We also show that participants do not distort their beliefs in response to financial incentives to do so, suggesting that deep values exert a stronger motivational force than financial incentives.
Keywords: C90; D72; D74; D83; P16; 330; Motivated Beliefs; Values; Polarization; Experiment; Reasoning